2015
DOI: 10.1186/s12885-015-1110-7
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-141 and miRNA-200b are closely related to invasive ability and considered as decision-making biomarkers for the extent of PLND during cystectomy

Abstract: BackgroundMicroRNAs (miRNAs) are small non-coding RNAs that silence their cognate target genes by specifically binding and cleaving messenger RNAs or inhibiting their translation. In this study, we explored whether miRNA-141 and miRNA-200b are involved in regulation of the invasive ability and epithelial–mesenchymal transition (EMT) of bladder cancer cells in vitro. We also evaluated their potential as biomarkers for deciding the extent of pelvic lymph node dissection (PLND) required during radical cystectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…This observation is in line with recent studies suggesting a lower expression of miRNA-200c in renal cell carcinoma and colorectal cancer 12. Similar studies suggesting low expression of miRNA-141 are available for bladder cancer23 and renal cell carcinoma 24…”
Section: Discussionsupporting
confidence: 91%
“…This observation is in line with recent studies suggesting a lower expression of miRNA-200c in renal cell carcinoma and colorectal cancer 12. Similar studies suggesting low expression of miRNA-141 are available for bladder cancer23 and renal cell carcinoma 24…”
Section: Discussionsupporting
confidence: 91%
“…In NSCLC, downregulated BCAR4 has been verified to exert an inhibitory effect on migration and metastasis by elevating the expression of E‐cadherin and downregulating that of N‐cadherin and vimentin (N. Li, Gao, & Liu, ). Additionally, it has been validated that upregulation of miR‐141 and miR‐200b expression can lead to MMP‐2, MMP‐9, vimentin, and N‐cadherin reduction, and E‐cadherin elevation in bladder cancer cells (Liu et al, ). Additionally, lncRNA UCA1 interference has been shown to regulate EMT, with increased E‐cadherin but decreased MMP‐7, N‐cadherin, and vimentin expression (Xiao, Wu, & Hu, ), which are consistent with the findings in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Among the miRNAs, the miR-200 family is proven to be directly associated with tumor metastasis and invasiveness (30)(31)(32). miR-200b, which is one of the members of the miR-200 family, has also been reported to have abnormal expression in various types of cancer, including bladder cancer and gastric carcinoma (33,34) PKCα belongs to the protein kinase C family and has been indicated to be involved in tumorigenesis, invasion, metastasis and proliferation (35)(36)(37). Previous studies of breast cancer indicated that PKCα could serve as an effective therapeutic target due to its notable mediator role in cancer (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%